Hyperoncotic dextran and systemic aprotinin in necrotizing rodent pancreatitis - Huch, Kristina; Schmidt, Jan; Schratt, W.; Sinn, Peter; Buhr, Heinz J.; Herfarth, Christian; Klar, Ernst (Scandinavian journal of gastroenterology, 1995)
Background: Dextrans improve pancreatic microcirculation in acute experimental pancreatitis. They could therefore facilitate the transport of a protease inhibitor to ischemic areas of tissue injury and be of additional benefit. Methods: To compare the effects of dextrans with and without aprotinin, necrotizing pancreatitis was induced in 33 male dextran-resistant Wistar rats by intraductal infusion of low-dose glycodeoxycholic acid (10 mmol/l) followed by intravenous cerulein (5 μg/kg/h) for 6 h. Three and four hours after the start of the cerulein infusion the animals received infusions of either Ringer's lactate (RL) (12 ml/kg), 70,000 Da dextran (10%) (DEX-70) (4 ml/kg) alone, or DEX-70 (4 ml/kg) with aprotinin (5000 IU/kg) (DEX-70/A). Results: The death rate was 60% within 9 h in the RL group (6 of 10) but only 10% in the DEX-70 group (1 of 10) (p < 0.03; Fisher's exact test) and 23% in the DEX-70/A group (3 of 13). Histomorphometry demonstrated a significant reduction of acinar necrosis in both treatment groups compared with control animals (p < 0.014; t test). Total amounts of trypsinogen activation peptides (TAP) in ascites were also significantly lower in these groups (p < 0.05; t test). Conclusions: DEX-70 given 3 h and 4 h after induction of pancreatitis significantly reduced the levels of TAP, limited acinar necrosis, and improved survival rate in acute necrotizing rodent pancreatitis. There was no additional benefit from the combination with aprotinin.